O papel da língua inglesa no contexto de globalização da economia e as implicações do uso das NTICs no processo de ensino aprendizagem desse idioma - Berger, Maria Amália Façanha (2005)
This study presents an analysis of the role that the English Language plays nowadays, and this is done by taking into account the implications of the uses of New Information and Communication Technology (ICT) in the teaching-learning process, as well as the changes that have been occurring in the work and education worlds, as a result of the process of globalization of the capitalist economy. Some reflections are also presented, related to the transformation that foreign language teaching has already been through up until the birth of what we know as the Communicative Approach, for this is the methodological path that is considered to be the most appropriate for the current needs of communication among different peoples. As a conclusion, this idiom, which is ever more present in different social instances - either in international commercial transactions or on the personal level, mainly when its use is directly connected to ICT - needs to be taught in a way that leads, more than at any other moment in history, to the development of communicative competence so that it will be in tune with the current context of information exchange at a global level. We believe that the use of ICT applied to the teaching of languages can become a valuable tool, as long as there is an understanding about the methodology that will support such pedagogical practice, because technology itself does not represent a teaching method, but a means that can either help in the transformation of the teaching process or give continuation to conservative pedagogical practices that do not answer the current demands of our society.